Aplikasi Kondensor pada Penyulingan Minyak Cengkeh di Desa Kare Kabupaten Madiun - Nur Ihda Farikhatin Nisa; Dyan Hatining Ayu Sudarni; Achmad Aminudin (Universitas Tribhuwana Tunggadewi Malang, 2019)
Clove oil is one of the essential oil products produced from Kare Village, Kare District, Madiun Regency. In the village there are several clove oil refining business groups, one of which is the